2014
DOI: 10.2355/isijinternational.54.2439
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and Nitrogen Distributions during Coal Carbonization and the Influences of These Elements on Coal Fluidity and Coke Strength

Abstract: The present study focuses on examining the fate of coal-S and coal-N during carbonization in detail and making clear the effects of these elements on coal fluidity and coke strength. When eight kinds of caking coals with 80-88 mass%-daf C are carbonized in high-purity He at 3°C/min up to 1 000°C with a quartzmade fixed bed reactor, 50-75% of coal-S remains as FeS and organic-S in the coke, and the rest is released as tar-S and H2S. Most of coal-N is also retained in the coke, and the remainder is converted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
0
22
1
Order By: Relevance
“…In addition, the N/C ratios for the 1200 and 1350 °C chars, normalized to that of the 1000 °C char, were lower at higher temperatures, irrespective of the coal type. These observations demonstrated that the N 2 increase was primarily due to char‐N after devolatilization …”
Section: Resultscontrasting
confidence: 57%
“…In addition, the N/C ratios for the 1200 and 1350 °C chars, normalized to that of the 1000 °C char, were lower at higher temperatures, irrespective of the coal type. These observations demonstrated that the N 2 increase was primarily due to char‐N after devolatilization …”
Section: Resultscontrasting
confidence: 57%
“…Coal tar pitch contains numerous hydrocarbons, 20) those that effectively increased the MD, such as coronene, those that hardly contribute to increase in MD, such as PAHs with molecular weights in the range 152.19-178. 23, and those that decreased the MD, such as PAHs containing oxygen. Since coal tar pitch contains an effective component, an ineffective component and an inhibitory component in MD, it is considered that the increase in MD when coronene was added was higher than when coal tar pitch was added.…”
Section: Dilatation and Interactions Between Coal And Hydrocarbon Reamentioning
confidence: 99%
“…20) In the previous study, changes in the fluidity of coal were investigated when several hydrocarbon reagents were used. For example, polycyclic aromatic hydrocarbons, 21) aromatic hydrocarbons containing nitrogen, [21][22][23][24] and aromatic hydrocarbons containing oxygen. 21,25) These investigations revealed that the fluidity of coal increased when a PAH with a high boiling point or an aromatic hydrocarbon containing nitrogen was used, but decreased when an aromatic hydrocarbon containing oxygen was used.…”
Section: Introductionmentioning
confidence: 99%
“…the interactions between coal and chemical substances. [8][9][10] Koyano et al 9) investigated influences of polycyclic aromatics on coal fluidity. They reported that polycyclic aromatics with higher molecular weight and higher boiling point had superior effect on coal fluidity and coke strength.…”
Section: Addition Effect Of Aromatic Amines On Coal Fluidity and Cokementioning
confidence: 99%
“…They reported that polycyclic aromatics with higher molecular weight and higher boiling point had superior effect on coal fluidity and coke strength. Tsubouchi et al 10) investigated the effect of nitrogen-containing aromatic compounds on coal fluidity and coke strength. And they reported that only indole was effective in improving coal fluidity and coke strength among nitrogen-containing aromatic compounds.…”
Section: Addition Effect Of Aromatic Amines On Coal Fluidity and Cokementioning
confidence: 99%